The coverage of children’s issues in Egyptian Newspapers - Serag, Eman Mohamed (AUC Knowledge Fountain, 2015)
This research is about analyzing a sample of the Egyptian newspaper’s coverage on issues related to children in order to determine the dominant subjects, images, and sources used to cover news/articles about or related to children. The purpose of the content analysis research is to give advocates a thorough grounding in the way children’s issues are being portrayed in the news. It is important to understand the current representation of the issues related to children in the Egyptian newspapers, to enhance childhood coverage in the future. Frames used in presenting news/articles and images used in portraying children, were discussed by applying the framing theory. Media hype concept was investigated as well in relation to the type and frequency of the news presenting children’s issues. In order to find out, the researcher examined three composite weeks of news coverage on children in four Egyptian major newspapers. The “victim frame” was most likely dominating both the independent and the governmental newspapers with 56% from the total news covered about children. Results also show that children’s social issues and problems received minimal coverage, as the percentage of portraying children as endangered was 13.4% from the total news/articles covered about children. Also, the distribution of news/articles according to the examined months assures that there is a relation between the type of news covered and hyping news.